Post-traumatic Stress Symptoms and Post-traumatic Growth in 223 Childhood Cancer Survivors: Predictive Risk Factors - Tremolada, Marta; Bonichini, Sabrina; Basso, Giuseppe; Pillon, Marta (Frontiers in Psychology, 2016)
With modern therapies and supportive care, survival rates of childhood cancer have increased considerably. However, there are long-term psychological sequelae of these treatments that may not manifest until pediatric survivors are into adulthood. The prevalence of post-traumatic stress disorder (PTSD) in young adult survivors of childhood cancer ranges from 6.2% to 22%; associated risk factors are young age at the assessment, female gender, low education level and some disease-related factors. The aim of this study was to investigate, in adolescent and young adult (AYA) survivors of childhood cancer, the incidence and severity of post-traumatic stress symptoms (PTSS), and to identify the risk factors and the associated post-traumatic growth (PTG) index. Participants were 223 AYA cancer survivors recruited during follow-up visits in the Oncohematology Clinic of the Department of Child and Woman’s Health, University of Padua. Data were collected from self-report questionnaires on PTSS incidence, PTG mean score, perceived social support, and medical and socio-demographic factors. Ex-patients’ mean age at the assessment was 19.33 years (SD = 3.01, 15-25), 123 males and 100 females, with a mean of years off-therapy of 9.64 (SD=4.17). Most (52.5%) had survived an hematological disorder and 47.5% a solid tumor when they were aged, on average, 8.02 years (SD=4.40). The main results indicated a moderate presence of clinical (≥9 symptoms: 9.4%) and sub-clinical PTSS (6-8 symptoms: 11.2%), with the avoidance criterion most often encountered. Re-experience symptoms and PTG mean score were significantly associated (r=0.24 p=0.0001). A hierarchical regression model (R2 = 0.08; F = 1.46; p = 0.05) identified female gender (β = 0.16; p = 0.05) and less perceived social support (β = -0.43; p = 0.05) as risk factors to developing PTSS. Another hierarchical regression model assessed the possible predictors of the PTG total score (R2 = 0.36; F = 9.1; p = 0.0001), with female gender (β = 0.13; p = 0.04), actual age (β = 0.52; p = 0.0001), younger age at the diagnosis (β = -0.3; p = 0.02), and less years off-therapy (β = -0.58; p = 0.0001) impacting on PTG.